Telehealth abortion services via Women on Web in Kenya (2013–2019): a descriptive analysis of the characteristics and motivations of the care seekers - Mary Achieng Ouma; Anita Alaze; Kenneth Juma; Hazal Atay; Rebecca Gomperts; Céline Miani (Sexual and Reproductive Health Matters)
In Kenya, access to abortion is legally restricted and allowed under a limited set of conditions. Teleabortion service providers, such as Women on Web (WoW), provide safe and effective abortion care outside the formal health sector. This study explores the characteristics and motivations of individuals in Kenya who completed an online consultation on the WoW website in 2013–2019. We used anonymised data provided by WoW to describe participants’ characteristics (n = 857) and their motivations for accessing the WoW online consultation (n = 449, since this information was only available for those who filled out the questionnaire from December 2017). Participants’ median age was 23; 65.0% did not have children, and 80.9% had not had a previous abortion. Pregnancies were caused by failure (43.6%) or absence of contraceptive method (49.0%), or rape (6.0%). The most frequently reported reasons for accessing the online consultation were legal restrictions and abortion costs. Those were selected by about half the participants (respectively 235 and 222/449). Next came the wish to keep the abortion private or secret, which was selected by 34.5% and 26.0% of participants. Among more positively framed reasons, home comfort came first (23.6%), followed by wanting to deal with the abortion oneself (20.7%) and finding an abortion through WoW empowering (17.4%). Abortion-seekers turning to teleabortion services usually do so following failing or absent contraception and to get access to safe abortions, avoid stigma, and keep their privacy. Expansion of teleabortion services, within or outside formal healthcare services, could strengthen abortion-seekers’ autonomy and agency in Kenya.